Application of N-Quinoline-2-carboxamido-8-aminoquinoline in Fabrication of a Ho(III)-PVC Membrane Sensor - Hassan Ali Zamani; Samaneh Langroodi; Soraia Meghdadi (E-Journal of Chemistry)
The N-quinoline-2-carboxamido-8-aminoquinoline (QCA) was used as a suitable ion carrier in the construction of a Ho(III) PVC-based membrane sensor. This sensor demonstrated good selectivity and sensitivity towards the holmium ion for a broad variety of cations, including alkali, alkaline earth, transition and heavy metal ions. The proposed electrode exhibits a linear dynamic range between 1.0×10-6 and 1.0×10-2 M, with a near Nernstian slope of 20.4±0.3 mV per decade and a detection limit of 4.2×10-7 M. The best performance was obtained with a membrane composition of 30% poly(vinyl chloride), 56% nitrobenzene, 2% sodium tetraphenyl borate, 10% oleic acid and 2% QCA. The potentiometric response of the constructed electrode is pH independent in the range of 2.4-7.4. The sensor possesses the advantages of short conditioning time, fast response time (∼ 5 s) and especially, good selectivity towards transition and heavy metal and some mono, di and trivalent cations. The Ho3+ sensor was successfully applied as an indicator electrode in the potentiometric titration of Ho(III) ions with EDTA. The electrode was also used for the determination of Ho3+ ions in mixtures of different ions and the determination of the fluoride ion in mouth wash solutions.